ANALISIS PENGELOLAAN LABORATORIUM IPA SMP NEGERI KOTA PEKANBARU - Rafica Zahara; Jimmi Copriady; Gimin Gimin (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2022)
The study aimed to determine the level of planning, organizing, implementing and supervising the management of science laboratory at Junior High School Pekanbaru, which is also seen from the gender and the type of school. In analyzing the data, the researches used a quantitative approach with the number of population was 56 head laboratories. Data collection methods are questionnaires and observations. To analyze the data, the researcher was used descriptive technique, sample t-test, and one way anova test. The results of the study showed the following 1) In the descriptive management of planning laboratories have an average of 4,168; organizing 4,254; supervision 3,815; and implementation of 4,118. 2) In the sample test the school type t-test found differences in planning and organizing, while the aspects of supervision and implementation there was no difference 3) In one way test the period of work found that planning and organizing 0-10 years and 11-20 years, 0-10 years and 21-30 years there are differences while there are no differences between 11-20 years and 21-30 years. Whereas the aspects of supervision and implementation there is no difference in all periods of work.